PENGARUH PENGUNAAN MEDIA PAPAN KARTU TEKA-TEKI UNTUK MEINGKATKAN PERKEMBANGAN KOGNITIF ANAK KELOMPOK B TK GENERASI HARAPAN KECAMATAN SUKODADI KABUPATEN LAMONGAN - Dina Fitriana (Universitas Islam Lamongan, 2019)
The problems in this study are: (1) how children's cognitive development; (2) is there any difficulty in using card board puzzle media; (3) whether there is influence of card board media on children's cognitive development. The purpose of this study is (1) to determine the level of cognitive development of children; (2) to find out the difficulty of using card board puzzle media; (3) to find out the influence of the card board puzzle media. The subjects in this study were students in the Generasi Harapan kindergarten group in Sukodadi Subdistrict which were registered in the 2018/2019 school year. There are 23 children. The results of the study in group B in TK Sukodadi District showed that of 23 children who were the subjects of research on cognitive development in using puzzle board card media to get to know the names of land vehicles. The design of this study uses the experimental results of data collection techniques used are observation and documentation. The analysis technique used is descriptive statistics and differential statistics.